Parameter monitoring and control in industrial sewing machines: an integrated approach - Carvalho, Helder (2008)
The industrial manufacturing of sewn products has always been one of the critical processes of the textile chain concerning quality assurance. Assuring the appropriate set-up and operation of all the machines, and thus the final seam quality, is a very complex task. Traditionally, this task is accomplished by empirical methods, with machine setting and quality control relying on the skills of operators and technicians. In this work, an approach to a more knowledge-based and integrated process planning and control is presented. A system was developed to measure and analyze the most important mechanical effects occurring during high-speed sewing. A general overview over this development is given in this paper.